Reevaluate secular trends of body size measurements and prevalence of hypertension among Chinese children and adolescents in past two decades. Issue 12 (December 2016) - Yan, Weili; Li, Xuesong; Zhang, Yi; Niu, Dayan; Mu, Kai; Ye, Ying; Liu, Fang
Abstract : Objective: This study reevaluated the secular trends of blood pressure and hypertension prevalence in Chinese children and adolescents by adjusting for growing body sizes. Methods: The study population was from the China Health and Nutrition Survey (1991–2011) and included 7358 boys and 6881 girls aged 8–17 years. Body size measurements and blood pressure were standardized into z -scores using national references to allow comparisons among different age groups and survey years. Prehypertension and hypertension rates were defined by using national and international age-specific and height-specific references. Results: SBP and DBP increased 0.07 and 0.09 SD per survey year, respectively. BMI, waist circumference, and height increased 0.14, 0.11, and 0.29 SD, respectively. The general obesity prevalence increased from 1.5 to 8.1% ( P trends ⩽ 0.0001), with an average annual increase (AAI) of 0.36 and 0.42% for urban and rural boys, respectively, and of 0.33 and 0.22% for urban and rural girls, respectively. The hypertension prevalence increased from 6.9 to 10.7% ( P trends ⩽ 0.0001). The overall AAI in hypertension was 0.19% and was three-fold higher among boys (0.29%) than among girls (0.09%), explaining the sex difference in the rural population. The area and sex differences in AAI remained after applying the international criteria. Conclusion: By adjusting for height, the hypertension prevalence in Chinese children increased 0.19% per year on average over the last two decades, which is much less than that reported in previous studies. This trend appears regardless of sex and area and is consistent with the obesity trend.